2020
DOI: 10.1101/2020.08.12.20173872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severity Assessment of COVID-19 based on Clinical and Imaging Data

Abstract: Objectives This study aims to develop a machine learning approach for automated severity assessment of COVID-19 patients based on clinical and imaging data. Materials and Methods Clinical data, including demographics, signs, symptoms, comorbidities and blood test results and chest CT scans of 346 patients from two hospitals in the Hubei province, China, were used to develop machine learning models for automated severity assessment of diagnosed COVID-19 cases. We compared the predictive power of clinical and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…To our knowledge, a few studies have adopted SHAP values to explain their models, but none have included SHAP plots to explain the model both on a local and a global level. 20 , 21 , 22 , 23 A 2020 study 20 on predicting acute kidney injury after cardiac surgery used a SHAP summary plot to explain the associations of the top 20 predictors with the outcome on the global level and the nonlinear association of several predictors. Fong et al 21 used a SHAP dependence plot to explain a 2-way interaction from a model to predict hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, a few studies have adopted SHAP values to explain their models, but none have included SHAP plots to explain the model both on a local and a global level. 20 , 21 , 22 , 23 A 2020 study 20 on predicting acute kidney injury after cardiac surgery used a SHAP summary plot to explain the associations of the top 20 predictors with the outcome on the global level and the nonlinear association of several predictors. Fong et al 21 used a SHAP dependence plot to explain a 2-way interaction from a model to predict hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Fong et al 21 used a SHAP dependence plot to explain a 2-way interaction from a model to predict hospital mortality. A third study 22 also used a SHAP summary plot to explore the top contributing factors that predicted illness severity among COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a wealth of information in the brain tumors including shape, texture, location, extent and distribution of involvement of the abnormality, that can be extracted by the lesion encoder. While it has been demonstrated in COVID-19 progression prediction [9] and severity assessment [15], here we demonstrated a new application of LE in patient OS prediction. It may have strong potential in a wide range of other clinical and research applications, e.g., brain tumor pseudo-progression detection [16] and ophthalmic disease screening [17].…”
Section: Lesionencoder Frameworkmentioning
confidence: 72%
“…In fact, many of the medical imaging studies that integrated heterogenous data have shown that data integration led to AI models with better performance compared to models built with imaging data alone. 53–55 , 62 , 65 , 69 , 76–78 Furthermore, although some data are difficult to get due to privacy issues or simply being unavailable, there are still a range of public data on risk factors that could be easily obtained for modeling. Many studies we reviewed leveraged the “free” data sources, such as the huge amounts of environmental data from the National Oceanic and Atmospheric Administration or the socioeconomic data from the Census Bureau.…”
Section: Discussionmentioning
confidence: 99%